Proximate Composition Of Fermented Maize-Soybean Composite Flour Blends (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
The objective of this study was to determine the proximate composition of fermented maize-soybean flour blend. Maize grains were sorted, cleaned, fermented for 48 h, oven dried (60 °C to constant weight), milled to flour and then sieved (250 μm) to produce maize Flour. The soybean was sorted, cleaned, boiled, cooled, dehulled, and fermented for 48 h with Rhizopus oligosporus (0.4g per 100g of beans), oven dried (60 °C to constant weight), milled and sieved (250 μm) to produce fermented soybean flour. Through mixture design, maize and soybean flours samples were blended in the ratios 90:10, 80:20, 70:30, 60:40, and 50:50 to obtain composite flours while 100% maize flour and 100% soybean flour served as controls. Proximate composition of the samples was evaluated using standard AOAC method. The results showed that the composite flours produced were more nutritious than the control flour samples. Carbohydrate was the most abundant, followed by the moisture content and the crude protein. Flour sample with 90:10 (Fermented maize:fermented soybean) had the highest carbohydrate content (70.91%). Flour sample produced with 50:50 fermented maiz:fermented soybean had the highest moisture (10.76%), crude protein (11.55%), crude fibre (4.78%), fat (3.35%) and ash (2.39%). Based on the findings from this research, it recommended that for nutritional enhancement and optimum complementation, flour blends of fermented maize and fermented soybean could be produced at a ratio of 50:50.
Keywords: Fermentation; Maize; Proximate; Rhizopus oligosporus; Soybean